Lokalitas Tafsir Al-Qur’an Minangkabau (Studi Tafsir Minangkabau Abad ke-20) - Aldomi Putra; Hamdani Anwar; Muhammad Hariyadi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Locality of Minangkabau in Interpretation of the Qur’an: (the study of Minangkabau interpretation of the 20th century)This study aims to find the absorption of locality in the interpretation of the Qur'an in Minangkabau, and to prove that Anthony H. Johns 'statement